2021
DOI: 10.1111/ppc.12854
|View full text |Cite
|
Sign up to set email alerts
|

The effect of affective learning on alexithymia, empathy, and attitude toward disabled persons in nursing students: A randomized controlled study

Abstract: Purpose To evaluate the effect of affective learning on alexithymia, empathy, and attitude toward disabled persons in nursing students. Design and Methods This prospective, randomized, controlled trial study was implemented among 70 nursing students. Based on transformative learning theory, the affective learning method was applied to the intervention group. Toronto Alexithymia Scale (TAS), Empathic Tendency Scale (ETS), and Attitudes Toward Disabled Person Scale (ATDPS) were administered to both groups. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In agreement with the findings of this current study, many researchers highlight that empathy is an essential ingredient in promoting relationships (Davis, 1990;Dincer & Inangil, 2022;Inslegers et al, 2012;Sevindi & Kumcagiz, 2017) Alexithymia can impair a person's ability to empathize, resulting in unavoidable communication difficulties.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with the findings of this current study, many researchers highlight that empathy is an essential ingredient in promoting relationships (Davis, 1990;Dincer & Inangil, 2022;Inslegers et al, 2012;Sevindi & Kumcagiz, 2017) Alexithymia can impair a person's ability to empathize, resulting in unavoidable communication difficulties.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the findings of this current study, many researchers highlight that empathy is an essential ingredient in promoting relationships (Davis, 1990 ; Dincer & Inangil, 2022 ; Inslegers et al, 2012 ; Sevindi & Kumcagiz, 2017 ), create a climate of trust, facilitate positive patient outcomes, reduce physiological discomfort, improve self‐awareness, etc. According to previous research, alexithymia affects 10% of healthy people (Sancar & Aktas, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[23] Empathy-based care also assists patients in reassessing their psychological state via transpersonal thinking and role-playing, thereby correcting misperceptions, further improving psychological status, raising expectation levels, and enabling a positive and optimistic attitude to face their illness, thus improving their quality of life. [24,25] The study also found a lower incidence of complications in the intervention group, likely attributable to the empathic care strategy’s encouragement of patient activity. Such activity not only enhances physical fitness but also helps regulate mood, alleviating negative emotions, promoting body fluid circulation, and preventing complications associated with prolonged bed rest.…”
Section: Discussionmentioning
confidence: 74%
“…This study describes three educational interventions: empathy-specific training, integrated curricula, and practice-oriented education. With 26 studies in support, most educational interventions for promoting empathy involved empathy-specific training, for example, communication skills training, intercultural nursing course, digital storytelling, narrative photography, and mindfulness-based empathy training (Ahmad et al, 2020; Arda Sürücü et al, 2021; Bas-Sarmiento et al, 2017, 2019; Can Gür & Yilmaz, 2020; Cannity et al, 2021; Chen et al, 2015; Çingöl et al, 2021; Dincer & Inangil, 2022; Ding et al, 2020; Eren & Gürhan, 2021; Fleming et al, 2015; Gholamzadeh et al, 2018; Goh et al, 2020; Hovland et al, 2021; Kimzey et al, 2019; Kyle et al, 2017; Lee et al, 2018; Leyva-Moral et al, 2021; Mikkonen et al, 2015; Petrucci et al, 2016; Petty et al, 2020; Suh et al, 2021; van Vliet et al, 2017; Yang et al, 2020; Yu et al, 2019). According to two studies (Celale Tangul et al, 2018; Heidke et al, 2018), integrated empathy curricula can also be considered in nursing education because the development of communication skills was improved more by integrated curricula than by conventional curricula.…”
Section: Main Theme 1: Promoting Empathymentioning
confidence: 99%